Relationships Between the Health Belief Model Constructs and Post-Stroke Patient Preferences in Choosing Acupuncture Therapy in Ngawi East Java - Cynthia Ayu Dian Puspitaningrum; Hanung Prasetya; Argyo Demartoto; Bhisma Murti; Revi Gama Hatta Novika (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Stroke is a serious medical condition that poses a significant risk of mortality and long-term disability, making it one of the leading causes of death and disability worldwide. Selecting an appropriate therapy is crucial to enhancing the quality of life among post-stroke patients. The Health Belief Model (HBM), which emphasizes individual beliefs regarding health and illness, is thought to play a pivotal role in influencing patients' decisions when choosing therapeutic interventions. This study aims to analyze the application of the Health Belief Model in the selection of acupuncture therapy among post-stroke patients. Subjects and Method: This study employed a cross-sectional design and was conducted in Ngawi Regency from October to December 2024. 200 samples of post-stroke patients were taken using the fixed disease sampling technique, consisting of 100 patients undergoing acupuncture and 100 patients undergoing physiotherapy. Dependent variables were the preference of acupuncture therapy and physiotherapy. Independent variables were perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. Data was collected using questionnaires and analyzed using path analysis on STATA 17. Results: The preference for acupuncture therapy was directly influenced by self-efficacy (b=3.41; CI95%=2.59 to 4.23; p<0.001). Self-efficacy to undergo acupuncture therapy was influenced by the perceived benefits (=2.75; CI95%=1.74 to 3.75; p<0.001), perceived barrier (b=-0.94; CI95%=-1.96 to 0.80; p<0.001), and cues to action (b=3.36; CI95%=2.32 to 4.40; p<0.001). Perceived benefit was influenced by perceived severity (b=1.25; CI95%=0.62 to 1.88; p<0.001). Conclusion: Self-efficacy directly influences the preference for acupuncture therapy. Meanwhile, the perceived benefit, the perceived barrier, and cues of action indirectly affect the preference for acupuncture therapy through self-efficacy. Perceived benefit was influenced by severity perception.